2022
DOI: 10.3389/fnmol.2022.842772
|View full text |Cite
|
Sign up to set email alerts
|

Glutamatergic Synapse Dysfunction in Drosophila Neuromuscular Junctions Can Be Rescued by Proteostasis Modulation

Abstract: Glutamate is the major excitatory neurotransmitter in the nervous system, and the Drosophila glutamatergic neuromuscular junctions (NMJs) offer a tractable platform to understand excitatory synapse biology both in health and disease. Synaptopathies are neurodegenerative diseases that are associated with synaptic dysfunction and often display compromised proteostasis. One such rare, progressive neurodegenerative condition, Spinocerebellar Ataxia Type 3 (SCA3) or Machado-Joseph Disease (MJD), is characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 114 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…These data suggest that MR6-26-2 partially improves proteostasis in the spinal cord of SOD1 G93A mice by facilitating the proper folding of mutant SOD1. We also analysed a neuromuscular junction pathology, since ebselen-derivative showed functional improvement of SOD1 G93A mice and proteostatic modulation rescued glutamatergic synaptic dysfunction in Drosophila neuromuscular junction 35 . Quantitative analysis of neuromuscular junctions in tibialis anterior muscles revealed that MR6-26-2 administration significantly ameliorated the denervation of skeletal muscles in SOD1 G93A mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These data suggest that MR6-26-2 partially improves proteostasis in the spinal cord of SOD1 G93A mice by facilitating the proper folding of mutant SOD1. We also analysed a neuromuscular junction pathology, since ebselen-derivative showed functional improvement of SOD1 G93A mice and proteostatic modulation rescued glutamatergic synaptic dysfunction in Drosophila neuromuscular junction 35 . Quantitative analysis of neuromuscular junctions in tibialis anterior muscles revealed that MR6-26-2 administration significantly ameliorated the denervation of skeletal muscles in SOD1 G93A mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, dEAAT1 loss induced hyperexcitability is partially rescued by insertion of human EAAT2, suggesting the hyperexcitability behavior is at least in part a consequence of glutamate transport deficiency and EAAT-associated glutamate uptake functions are conserved between Drosophila and mammals ( Rival et al, 2004 ). Furthermore, Drosophila has been widely used as a model organism to test modulation of glutamate-mediated neurodegeneration ( Agrawal et al, 2005 ; Martin and Krantz, 2014 ; Chakravorty et al, 2022 ). For example, riluzole, an anti-excitotoxic agent that increases glutamate uptake has been shown to rescue memory deficits in Drosophila ( Matsuno et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%